Preparative isolation of a novel flavonoid from an infusion of Byrsonima basiloba leaves by high-speed counter-current chromatography - Sannomiya, Miriam [UNESP]; Figueiredo, Maria E. [UNESP]; Da Silva, Marcelo A. [UNESP]; Rodrigues, Clenilson M. [UNESP]; Dos Santos, Lourdes C. [UNESP]; Souza-Brito, Alba R.M.; Vilegas, Wagner [UNESP] (SAGE Publications, 2007)
A method for the isolation of three compounds from the infusion of leaves of Byrsonima basiloba A. Juss. by high-speed counter-current chromatography (HSCCC) was developed. This technique led to the separation of a novel compound, quercetin 3-O-α-L-rhamnopyranosyl-(1→3)-O-[α-L- rhamnopyranosyl-(1→6)]-β-D-allopyranoside, and two known compounds quercetin-3-O-α-L-rhamnopyranosyl-(1→6)-β-D-galactopyranoside and (+)-catechin in 4 h with purities of over 92%. The structures of the compounds were determined by one- and two-dimensional NMR spectroscopy and HPLC.
Keywords: Byrsonima basiloba; Counter-current chromatography; Flavonoids; Gradient elution